The Influence of Promotions and Prices on Consumer Satisfaction at Pontis Kopi & Yard Sukabumi Regency - Sudarijati; Titiek Tjahja Andari; Alfira Syahrani (International Journal of Integrated Science and Technology, 2024)
Consumer satisfaction is the level of a person's feelings when receiving the product or service offered and comparing the performance of the product or service received with the expectations they have. This study aims to determine the effect of promotion and price on customer satisfaction at Pontis Coffee & Page Sukabumi Regency. This study uses descriptive and verification research with a survey method. The sample in this study were 100 people using non a probability sampling technique with an accidental sampling procedure. Data collection techniques through interviews, observations, questionnaires and literature studies. The data analysis used is multiple linear regression analysis. The results showed that simultaneously and partially the promotion and price variables had a positive and significant effect on consumer satisfaction at Pontis Coffee & Page Sukabumi Regency